Muslim Women in India: Status of Demographic, Socioeconomic and Health Inequalities. Issue 3 (2nd July 2020) - Ohlan, Ramphul
Abstract: This paper examines the comparative status of demographic, socioeconomic and health inequalities experienced by Muslim minority women in the Indian context. To do so, the socioeconomic conditions of Muslim women are compared with those of other minorities and majority religions by using the latest available data. The empirical analysis indicates that Muslim women are relatively educationally and economically backward in India. The socioeconomic condition of women of almost all other minorities is better off than that of Muslims. The paper also goes to examine the level of economic freedom enjoyed by the women of different minorities. It is found that the participation of women of the Muslim minority in household economic decision-making is relatively low. The findings of this study provide justification for the continuation of the provision of special treatment for Muslim women through government policies for improving the level of their socioeconomic development.